Biocompatible pH-responsive nanoparticles with a core-anchored multilayer shell of triblock copolymers for enhanced cancer therapy. Issue 23 (12th May 2017) - Ellis, Elizabeth; Zhang, Kangyi; Lin, Qianyu; Ye, Enyi; Poma, Alessandro; Battaglia, Giuseppe; Loh, Xian Jun; Lee, Tung-Chun
Abstract : pH-Responsive drug nanocarriers were made via facile self-assembly, showing excellent stability in bio-media (50% PBS/FBS) and enhanced drug efficacy towards cancer cells. Abstract : Drug nanocarriers are synthesised via a facile self-assembly approach using gold nanoparticles (Au NPs) as a structural core. The nanocarriers feature a multilayer shell of POEGMA–PDPA–PMPC triblock copolymers with a chain-end thiol functional group for anchoring to the Au NP surface. This water-soluble triblock copolymer was synthesised via atom transfer radical polymerisation (ATRP) from a bi-functional initiator containing a disulphide bridge. The resultant nanocarriers exhibit high biocompatibility plus excellent colloidal stability and antifouling capability in bio-media (50% PBS/FBS). Encapsulation and release of a hydrophobic drug can be effectively triggered by a pH-stimulus. Meanwhile drug-loaded nanocarriers show enhanced efficacy towards cancer cells compared to plain drug.